A systematic literature review of the factors influencing hearing protection device usage among industrial workers - Nur Syafiqah, Fauzan; Ezrin Hani, Sukadarin; Widia, Mirta; Irianto, Irianto; Ihwan, Ghazali (MDPI, 2023)
This systematic literature review (SLR) aims to determine the factors influencing the use of hearing protection devices (HPDs) among industrial workers. This study was guided by the PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method, and four databases comprising Scopus, Science Direct, PubMed, Wiley Online Library, and Google Scholar were employed. A total of 196 articles were identified, and 28 studies on the factors associated with HPD use among industrial workers from 2006 to 2021 met the inclusion criteria. Resultantly, five main themes emerged from this review: sociodemographic (29%), interpersonal influences (18%), situational influences (18%), cognitive-perceptual (29%), and health-promoting behavior (6%) associated with HPD use among industrial workers. A total of 17 sub-themes were identified, including age, gender, educational level, noise level, working experience, social models, interpersonal support, social norms, safety climate, training, organizational support, perceived barrier, perceived susceptibility, perceived severity, perceived benefit, self-efficacy, and cues to action. The significant factors influencing workers to use HPDs are sociodemographic, interpersonal influences, situational influences, and health-promoting behavior. Future studies should focus on the cues to action toward human behavior influencing the use of HPDs, workers’ health status, and comorbidities of hearing loss. Therefore, this systematic study gives valuable reference resources for up-and-coming researchers as well as new knowledge to expert professionals and academics in various industries.